2017
DOI: 10.1016/j.ensci.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, factor analysis and internal consistency calculation of the Insomnia Severity Index (ISI) in French and in English among Lebanese adolescents

Abstract: ObjectivesOur goal is to validate and to verify the reliability of the French and English versions of the Insomnia Severity Index (ISI) in Lebanese adolescents.Study designA cross-sectional study was implemented.Methods104 Lebanese students aged between 14 and 19 years participated in the study. The English version of the questionnaire was distributed to English-speaking students and the French version was administered to French-speaking students. A scale (1 to 7 with 1 = very well understood and 7 = not at al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 35 publications
4
31
0
Order By: Relevance
“…According to these guidelines, individuals can be categorized as having no clinically significant insomnia (0–7), subthreshold insomnia (8–14), clinically significant insomnia (moderate severity; 15–21), or clinically significant insomnia (severe; 22–28). The ISI has demonstrated good internal consistency (Chahoud, Chahine, Salameh, & Sauleau, ; Morin, Belleville, Belanger, & Ivers, ), test–retest reliability (Chahoud et al, ), convergent, and discriminant validity (Bastien et al, ; Morin et al, ) and is sensitive to changes in perceived sleep difficulties following treatment (Bastien et al, ). Moreover, scores on the ISI converge with reports by clinicians and significant others (Bastien et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…According to these guidelines, individuals can be categorized as having no clinically significant insomnia (0–7), subthreshold insomnia (8–14), clinically significant insomnia (moderate severity; 15–21), or clinically significant insomnia (severe; 22–28). The ISI has demonstrated good internal consistency (Chahoud, Chahine, Salameh, & Sauleau, ; Morin, Belleville, Belanger, & Ivers, ), test–retest reliability (Chahoud et al, ), convergent, and discriminant validity (Bastien et al, ; Morin et al, ) and is sensitive to changes in perceived sleep difficulties following treatment (Bastien et al, ). Moreover, scores on the ISI converge with reports by clinicians and significant others (Bastien et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The ISI is a 7-item self-report instrument that measures symptoms and insomnia-related problems. The scale has been validated and is widely used in insomnia studies (32)(33)(34). The total ISI score ranges from 0 to 28; higher scores indicate more severe insomnia.…”
Section: Insomniamentioning
confidence: 99%
“…Each item has a 5-point Likert scale used for rating. Studies have shown a cutoff score of 14 has a sensitivity and specificity of 94% which could distinguish most cases of insomnia from normal controls, hence we adopted this cutoff for our study [9,10,[12][13][14].…”
Section: Main Outcomementioning
confidence: 99%